Priority directions for the development of small business and private entrepreneurship in Uzbekistan - Zhusupova Anzhim Tansykbaevna (THE INNOVATION ECONOMY, 2026)
The article considers the priority areas of development of small business and entrepreneurship in the Republic of Uzbekistan, including improving the regulatory environment, financial support, digitalization, export support, encouraging women's and youth entrepreneurship, environmental sustainability. The study is based on an analysis of the regulatory framework and practical examples.